Samson, Cecil, and Lion Imagery within DeMille's Samson and Delilah - Kozlovic, Anton Karl (Journal of media and religion, 2009)
Cecil B. DeMille was one of the founders of Hollywood, a progenitor of Paramount studio, and a master of the American biblical epic who produced and directed Samson and Delilah (1949). To the public, Samson is a heroic good guy, but scripturally speaking he is the nadir of the 12 judges overseeing Israel's religio-political disintegration (Judg. 13-16). DeMille-the-Episcopalian-Christian subtextually constructed his Old Testament Samson as a New Testament Christ-figure and then buttressed this holy design with New Testament-resonating lion imagery to further uprate Samson's sagging sanctity. Utilizing humanist film criticism as the guiding analytical lens coupled with a selective review of the critical DeMille, film, and religion literature, this frequently unappreciated leonine thematic is explicated herein. It is concluded that DeMille's celluloid Samson was cleverly constructed and that, overall, he was a defter biblical filmmaker than hitherto appreciated. Further research into DeMille studies, biblical epics, and the emerging interdisciplinary field of religion-and-film is recommended.